HLC Pair Suppression as a Risk Factor for Bacterial Bloodstream Infections and Early Mortality in Newly Diagnosed Intact Immunoglobulin Multiple Myeloma Patients - Garcia de Veas Silva, Jose Luis; Gonzalez Cejudo, Maria Trinidad; Garcia Perojil Jimenez, Alberto; Garcia Lopez Velez, Maria del Señor; Garcia Rios Tamayo, Rafael; Garcia Bermudo Guitarte, Carmen; Garcia De Haro Muñoz, Tomas (Frontiers in Oncology, 2021)
Despite the outstanding progresses in Multiple Myeloma treatment options in the last decades, it remains an incurable disease nowadays. Infectious events are a complication due to an impaired immune system associated with MM, sometimes a life-threatening one, particularly on the first months after the diagnosis. Both the underlying disease and treatment can contribute to the infection risk, so a biomarker that assess this risk could be highly relevant for a more tailored management of the patient. The measurement of the heavy+light chain (HLC) pairs of immunoglobulins in serum allows the quantification of both the monoclonal component and the non-monoclonal immunoglobulin of the same isotype. This approach has demonstrated high sensitivity for the detection of the clonality and prognostic value for MM. HLC pair suppression itself has prognostic power and it has been proposed to be a reflection of the immune system’ attempt to control the tumor. In this study we evaluated the impact of the HLC pair suppression on the rate of bloodstream infections (BSI) and early death in 115 newly diagnosed MM patients. 21% of the patients suffered a BSI in the first 6 months after diagnosis, of which 58% died within this period, accounting to 67% of the early deaths in global and highlighting the major impact of infections on MM patients in a “real world” setting. Severe HLC pair suppression identified patients with a higher risk of early BSI (HR: 6,97, p=0,009), and extreme HLC pair suppression together with BSI event and age>65 were independent risk factors for early death (p<0,001). Based on these factors, a stratification model was generated to identify patients at a higher risk of early death and poorer OS, with an apparently better performance than the ISS on the early death context. In conclusion, HLC pair suppression associates with both a higher risk of life-threatening early infection and early death in newly diagnosed MM patients. Patients older than 65 with extreme HLC pair suppression and BSI are at a high risk of early death, and thus patients presenting with these criteria have a very adverse prognosis.